Економічна додана вартість як показник ефектив¬ності діяльності підприємства - Піменова, Ю.І. (Стратегія і механізми регулювання промислового розвитку, 2017)
Розглянуто питання еволюції поняття доданої вартості; на основі аналізу різних формулювань надано визначення цього поняття та його значення в сучасному світі. Проаналізовано ключові переваги та недоліки показника економічної доданої вартості. Досліджено можливість використання концепції економічної доданої вартості у фінансовому управлінні підприємствами України. Рассмотрены вопросы эволюции понятия добавленной стоимости; на основе анализа различных формулировок дано определение этого понятия и его значения в современном мире. Проанализированы ключевые преимущества и недостатки показателя экономической добавленной стоимости. Исследована возможность использования концепции экономической добавленной стоимости в финансовом управлении предприятиями Украины. The economic nature of value added determines the nature of socioeconomic relations in society in the sphere of property relations. In the economic literature, there are many definitions of this category. However, at present neither in Ukraine nor abroad there is a clear formulation of the notion of value added. Analyzing the different formulations of this concept, we can conclude that the added value is the cost of the goods, added by its processing, that is, the value of the product, minus the cost of materials used for its production. In the modern world, the value of the value added indicator is growing. This is explained, firstly, by the fact that value added is directly dependent on the degree of efficiency of the enterprise's performance, and secondly, it acts as a basic source of generating revenue items for the state budget, since it can be a factor in increasing the competitiveness and capitalization of enterprises in аs a result of which the state and economic entities are potentially interested in its growth simultaneously. Since the 90s of the last century, the indicator of economic added value became an important financial indicator as the leading American companies. Economic added value (EVA) represents the profit of an enterprise from ordinary activities after deduction of taxes, reduced by the amount of payment for the entire capital invested in the enterprise. The essence of EVA is manifested in the fact that this indicator reflects the addition of value to the market value of the company and an assessment of the effectiveness of the enterprise for determining how this enterprise is valued by the market. Western companies use the EVA concept as a more effective measure of unit performance than net profit, due to the fact that EVA evaluates not only the final result, but also how much capital and at what price was used. The value of EVA determines the behavior of the owners of the enterprise in relation to the investment of capital in this enterprise. In this paper, we consider possible options for the relationship between the value of the EVA indicator and the behavior of owners, outlines the main ways to increase this indicator, and also analyzes the main advantages and disadvantages of its use. The possibility of using the concept of economic added value in the financial management of Ukrainian companies is determined.